Beyond Usability: Modeling User Satisfaction in Alumni Networking Platforms Using WebQual 4.0 and SEM-PLS - Grace Kilmaskossu; Sfenrianto (CV. Creative Tugu Pena, 2026)
This study examines the effect of website quality on user satisfaction using the WebQual 4.0 framework in the context of an alumni networking platform. The study aims to determine which dimension—usability quality, information quality, or service interaction quality—has the most dominant influence on user satisfaction. A quantitative approach was employed using a survey method, with data collected from 298 respondents through purposive sampling. The data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS 4. The results indicate that the research model has moderate explanatory power, with an R² value of 0,495, meaning that 49,5% of user satisfaction is explained by the three website quality dimensions. Hypothesis testing reveals that service interaction quality has a positive and significant effect on user satisfaction (β = 0,440; p < 0,001; f² = 0.239) and is the most dominant factor. Information quality also has a positive and significant effect (β = 0,329; p < 0,001; f² = 0,133). In contrast, usability quality does not have a significant effect (β = 0,090; p = 0,059; f² = 0,016), indicating that usability is perceived as a basic requirement rather than a primary driver of satisfaction. These findings indicate that user satisfaction is primarily influenced by service interaction quality, followed by information quality.